2016
DOI: 10.1002/mnfr.201500711
|View full text |Cite
|
Sign up to set email alerts
|

Plasma fatty acid patterns reflect dietary habits and metabolic health: A cross‐sectional study

Abstract: Distinct fatty acid patterns were identified which were related to demographics, dietary habits, and metabolic profile. A pattern higher in VLCSFA and lower in ALA was associated with healthier metabolic outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 41 publications
1
40
0
Order By: Relevance
“…Previous studies have reported FA patterns, derived from different components of blood and tissue in association with obesity 29 and the MetS, 22,30 but not with dietary patterns. These patterns were generated by varying numbers of FAs ranging from nine to 34 FAs, 22,29,30 and some included estimated desaturase activities, 30 by means of use of factor 29,30 and cluster 22 analysis. Consequently, these derived patterns differed from that obtained in our study.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Previous studies have reported FA patterns, derived from different components of blood and tissue in association with obesity 29 and the MetS, 22,30 but not with dietary patterns. These patterns were generated by varying numbers of FAs ranging from nine to 34 FAs, 22,29,30 and some included estimated desaturase activities, 30 by means of use of factor 29,30 and cluster 22 analysis. Consequently, these derived patterns differed from that obtained in our study.…”
Section: Discussionmentioning
confidence: 96%
“…13 Positive associations of serum phospholipid C20:3n-6 with BMI, as well as total n-6 PUFAs with waist:hip ratio were also documented in a study of Mexican women. 17 Some studies also report positive associations of specific plasma phospholipids n-6 PUFAs with metabolic risk, 18,22 while other studies report inverse associations of total n-6 PUFAs in erythrocytes and serum, respectively, with the MetS. 23,24 Due to inconsistent results in different studies relating to circulating n-6 PUFAs, further research to understand their role in association with obesity and the MetS is highly recommended.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Participants in the present study also provided a fasting blood sample. Collection and processing of blood samples has previously been described .…”
Section: Methodsmentioning
confidence: 99%
“…Participants in the present study also provided a fasting blood sample. Collection and processing of blood samples has previously been described [38,40]. Anthropometric measurements were also taken by the researcher in the participant's home and included weight (kg), height (m) and body composition.…”
Section: Dietary Data Collection Biofluid Collection and Anthropometrymentioning
confidence: 99%